Estimation of the soil erosion and sediment trapping using Gerlach troughs in different Land Uses in Luangprabang Province - PHIHMALATH, Soubanh; CHANTHAKHOUN, Vongpasith; MANYSOAT, Soutthanou (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aims to study sediment loss in different areas by collecting data from the Reservoir and Gerlach troughs in the Luangprabang Province, Laos The implementation of this experiment was a selection of study areas to install soil sediment retention tools (Gerlach trough) according to 6 treatments such as T1: No teak+Ruzi grass; T2: No teak + Fallow; T3: Teak with low understory density + Natural regrowth; T4: Teak with low understory density + Ruzi grass; T5: Teak with high understory density+ Natural regrowth; T6: Teak with high understory density+ mixed fodder cover (Ruzi and Napier grass). In 3 replicates/treatments by RCBD design, a total of 18 instruments will be installed by installing them in a row on both sides of the soil, to trap the soil sediment that flows with the water, then there will be a collection of samples that can be collected, and then filter the soil sediment and dry it at a temperature of 105 degrees, for a period of 48 hours and calculate the amount of soil sediment loss in the area. Results found that the highest soil loss (sediment) was in the area planted teak with low understory density + Natural regrowth (T3) followed by the area planted teak with low understory density + Ruzi grass, (T4), and the lowest soil loss was in the area no teak+Ruzi grass (T1) and the area no teak + fallow (T2). While the highest surface water runoff was in the area planted teak with low understory density + Natural regrowth (T3) and the area planted teak with low understory density + Ruzi grass, (T4). On the other hand, factors that are related to surface water runoff and soil sediment loss such as percentage of land cover density, slope of the land, and residue or humus on the land were found that the area no teak with planted Ruzi grass and the area no teak with fallow (natural growth) had lowest rate of surface water runoff and lowest soil sediment loss compared to other areas. It can be concluded that the land cover factor has an important role in helping to reduce surface water runoff and help prevent soil sediments from being lost to runoff in agricultural land and upland cultivation.